Molecular Mechanisms and Effectiveness of Sports On Hypertension Treatment - Nasution, Sharlini Desfika; Rahmi, Rahmi (Universitas Muhammadiyah Sumatera Utara, 2024)
Abstract: Hypertension is a serious global health problem. Exercise is an effective non-pharmacological intervention in the management of hypertension through several molecular mechanisms, including vascular endothelial regulation, oxidative stress modulation, and anti-inflammatory effects. This literature study aims to increase readers' knowledge about the molecular mechanism and effectiveness of exercise in the treatment of hypertension by conducting literature searches in national and international journals published in the last 5 years. The main pathological changes in hypertension are changes in the structure and function of arterial vessels, which are characterized by increased peripheral vascular resistance due to vascular remodelling. Regular aerobic exercise has been shown to increase the activity of antioxidant enzymes, including superoxide dismutase (SOD), which plays an important role in protecting cells from oxidative damage. The frequency and duration of exercise play a key role in the effectiveness of exercise programs to lower blood pressure in hypertensive patients.